Adsorption‐Catalysis Design in the Lithium‐Sulfur Battery. Issue 2 (19th November 2019) - Zhang, Miao; Chen, Wei; Xue, Lanxin; Jiao, Yu; Lei, Tianyu; Chu, Junwei; Huang, Jianwen; Gong, Chuanhui; Yan, Chaoyi; Yan, Yichao; Hu, Yin; Wang, Xianfu; et al.
Abstract: Lithium‐sulfur (Li‐S) batteries are one of the most promising next‐generation energy‐storage systems. Nevertheless, the sluggish sulfur redox and shuttle effect in Li‐S batteries are the major obstacles to their commercial application. Previous investigations on adsorption for LiPSs have made great progress but cannot restrain the shuttle effect. Catalysts can enhance the reaction kinetics, and then alleviate the shuttle effect. The synergistic relationship between adsorption and catalysis has become the hotspot for research into suppressing the shuttle effect and improving battery performance. Herein, the adsorption‐catalysis synergy in Li‐S batteries is reviewed, the adsorption‐catalysis designs are divided into four categories: adsorption‐catalysis for LiPSs aggregation, polythionate or thiosulfate generation, and sulfur radical formation, as well as other adsorption‐catalysis. Then advanced strategies, future perspectives, and challenges are proposed to aim at long‐life and high‐efficiency Li‐S batteries. Abstract : This review focuses on the adsorption‐catalysis design in the lithium‐sulfur (Li‐S) battery. This includes adsorption‐catalysis for lithium polysulfides aggregation, adsorption‐catalysis for thiosulfate or polythionate generation, adsorption‐catalysis for sulfur radical formation, and other adsorption‐catalysis in Li‐S batteries.